Characterization of Bioactive Compounds and Stability of Mangrove Extract Rhizopora Sp. - Dirk Y. P. Runtuboi; Ervina Indrayani; Imam Mishbach; Gabriela Olivia Karisoh (Jurnal Penelitian Pendidikan IPA, 2024)
In recent decades, bioactive compounds contained in plants have increasingly attracted the attention of researchers. This is because these bioactive compounds have the potential to be used as raw materials in the manufacture of health products, medicines, and cosmetics. However, in developing products based on bioactive compounds in Rhizopora sp. mangroves, sufficient knowledge about these compounds is needed. The main objective of this study was to identify bioactive compounds and evaluate the stability of Rhizopora sp. mangrove extract obtained from Youtefa Bay area, Jayapura City. The methods used include mangrove leaf sampling, maceration extraction using methanol, followed by fractionation and phytochemical tests to detect the content of active compounds. Data analysis was performed using UV and IR spectroscopy. The results showed that the isolated Rhizophora sp. mangrove leaf extract obtained from Youtefa Bay waters contained several bioactive compound activities such as alkaloid, flavonoid, phenolic, and saponin bioactive compound groups in methanol solvents.  In conclusion, mangrove Rhizophora sp. from Youtefa Bay has great potential as a source of bioactive compounds that can be further developed in various commercial products.